A REVIEW OF JOB STRESS AND ITS INFLUENCE ON HEALTH-RELATED RISK - Nur’Aina Samaniah Binti Osman; Siti Musliha Binti Mohd Idris; Nurul Nabilah Binti Shaare; Mira Aishwarya Ain Mira Hussein; Wan Khayrina Sofiya Binti Mohd Hasnurizal; Nurul Illya Batrisya Binti Aziz (International Journal of Accounting, Finance and Business, 2022)
Job stress can contribute to a variety of health issues. For instance, heart diseases, psychological health, and cardiovascular disorders are examples of health-related problems caused by job stress. Job stress is a common reaction that arises when the workload increases to the point of becoming excessive. This review study is intended to add information and literature on the job stress and its influence on health-related risk. Through literature review, it will focus on job stress issues that lead to health-related risk and how preventive action can be taken to reduce job stress. Based on the review from the selected articles, there are 23 health risks or health problems that we observed such as lack of appetite, increased heart rate and diabetes and 16 preventions that have been taken from 20 articles. For example, sleep on time, engaging in hobbies and gatherings. As individuals, we must be able to cope with and manage work-related stress because even if you are enthusiastic about what you do, any profession may have stressful parts. Work-related stress, on the other hand, can become overpowering when it becomes chronic, causing harm to both physical and emotional health and will become a longterm illness if not taken care of quickly. This review will provide as a guide or benefit for managers and employers in planning for a healthy workplace and positive preventive measures.